2021
DOI: 10.1364/ome.427686
|View full text |Cite
|
Sign up to set email alerts
|

High refractive index IR lenses based on chalcogenide glasses molded by spark plasma sintering

Abstract: In this work, spark plasma sintering is used to mold non conventional chalcogenide glasses of high refractive index at low temperature (<400°C). This equipment, usually used for sintering refractory materials, is presented as efficient for both densification and high precision molding of IR transparent bulks and lenses of telluride glasses. Thermo-mechanical and optical characteristics of the selected Ge25Se10Te65 glass composition were investigated showing a refractive index of 3,12@10 µm and with however … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The preparation of chalcogenide glass disks by powder hot‐pressing technique is usually carried out at a temperature of tens of degrees to ∼100°C above the T g 21,33,34 . It has been proposed that the powders with different n for GRIN glass preparation should have similar T g , 11 so they can be hot‐pressed together at the same temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation of chalcogenide glass disks by powder hot‐pressing technique is usually carried out at a temperature of tens of degrees to ∼100°C above the T g 21,33,34 . It has been proposed that the powders with different n for GRIN glass preparation should have similar T g , 11 so they can be hot‐pressed together at the same temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The preparation of chalcogenide glass disks by powder hot-pressing technique is usually carried out at a temperature of tens of degrees to ∼100 • C above the T g . 21,33,34 It has been proposed that the powders with different n for GRIN glass preparation should have similar T g , 11 C vs. 249 • C), reasonably α difference (3.8 ppm/K), large Δn (∼.48@10 µm), and therefore are chosen for evaluating the suitability of fabricating GRIN glasses using these glass powders. To evaluate the optical properties of Ge 20 As 20 Se 20 Te 40 and Ge 12 As 22 Se 66 glasses prepared by powder hot-pressing technique, the glass powders with size of 125-150 µm were hot pressed to compact glasses at 300 • C and 40 MPa for 5 min, and compared with the melt-quenched glass.…”
Section: Glass Compositionsmentioning
confidence: 99%
“…In this context, developing a process that allows for making a near-shape or even finished IR optics by using residual glass may be of high interest. In Ref [13], Univ. of Rennes demonstrated that flash SPS sintering gives the possibility to shape lenses from raw powder rapidly and reproducibly.…”
Section: Study Of High-index Chalcogenide Glass For Vga Sensorsmentioning
confidence: 99%
“…High-index Chalcogenide glasses are therefore of great interest and Univ. of Rennes is currently developing TGG [8] and TGS glasses [13] that have an index of refraction greater than 3.…”
Section: Design Study With High-index Chalcogenide Glass For Vga Sensorsmentioning
confidence: 99%
“…Common commercial infrared imaging systems typically consist of a combination of infrared crystals and ChGs. Typical infrared crystals such as ZnSe/S and Ge are used as part of the imaging system components, and are difficult to modify in the imaging system because their optical properties are determined by a fixed crystal structure [5][6][7]. ChGs are non-oxide amorphous compounds based on S, Se and Te and combined with Ge, As, Sb, Ga, Ag, Pb, etc.…”
Section: Introductionmentioning
confidence: 99%